Vitamin D, Body Mass Index, and Total Lymphocyte Count in Drug-Sensitive and Drug-Resistant Tuberculosis Patients in Banjarmasin - Riefani, Soraya; Juhairina, Juhairina; Isa, Mohamad; Kusumawardhani, Erna; Haryati, Haryati; Syam, Shaogi; Nurrasyidah, Ira (Jurnal Respirasi, 2024)
Introduction: Tuberculosis (TB) remains a global health problem that causes high morbidity and mortality. Based on its classification, TB is divided into drug-sensitive (DS) and drug-resistant (DR). Several risk factors susceptible to TB are malnutrition with low body mass index (BMI), vitamin D deficiency (VDD), and low total lymphocyte count (TLC) related to low immune status. This study aimed to examine the relationship between vitamin D (VD), BMI, and TLC in the TB population in Banjarmasin. Methods: This was an analytic observational study with a cross-sectional design. The total study sample was 42 patients, confirmed by rapid molecular testing, who had not been treated for TB in Banjarmasin from January to May 2023 and met the inclusion and exclusion criteria. Chi-Square and Fisher's exact statistical tests were used to see the relationship between VD, BMI, and TLC in DS TB and DR TB. Results: The median age of DS TB was 38 (24-52) years old, and DR TB was 51 (37-58) years old. Most of the gender was male (24 patients/57.1%). There was a statistically significant difference between VD and BMI in DS TB and DR TB (p = 0.048; p = 0.019). There was a significant relationship between VD and TLC in DS TB and DR TB (p = 0.048). Conclusion: VD and BMI significantly differed in DS TB and DR TB. There was a significant correlation between VD and TLC in TB patients.